Pengaruh Edukasi Media Platform Tiktok Terhadap Pengetahuan Penderita Hipertensi di Wilayah Kerja Puskesmas Cireunghas - Rika Rahayu; Irawan Danismaya; Arfatul Makiyah (Jurnal Ventilator, 2024)
Hypertension is still a significant problem in the global health sector today. The general public recognizes this condition as "high blood pressure" because blood pressure increases beyond the normal threshold. Health education has a major role in increasing public understanding about hypertension. So media outreach using the Tiktok social media platform can expand public knowledge and understanding regarding the urgency of hypertension. Objective: To determine the influence of the TikTok educational media platform on the knowledge of hypertension sufferers. Method: The design in this research uses a quasi-experimental approach using a one group pretest posttest design. Results: based on the results of statistical tests using the Paired Samples Test, the resulting P value is 0.000 < 0.05. Conclusion: it can be concluded that there is an influence of the TikTok educational media platform on the knowledge of hypertension sufferers in the Cireunghas Health Center working area. Suggestion: It is recommended for future researchers to measure the influence of respondent characteristics such as age, gender, education level, length of time suffering from hypertension, type of work and type of anti-hypertensive medication used on the knowledge of hypertension sufferers